2013
DOI: 10.1093/ehjci/jes303
|View full text |Cite
|
Sign up to set email alerts
|

Incremental diagnostic accuracy of hybrid SPECT/CT coronary angiography in a population with an intermediate to high pre-test likelihood of coronary artery disease

Abstract: In > 40% of the patients with a high pre-test likelihood no significant CAD was demonstrated, emphasizing the value of accurate pre-treatment cardiovascular imaging. Hybrid SPECT/CCTA was able to accurately diagnose and exclude significant CAD surpassing standalone myocardial SPECT and CCTA, vs. a reference standard of FFR measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…In addition, the CT was used only for reconstructing attenuation maps and AC in these CT AC studies. We propose that if scatter correction (39) and anatomic information such as coronary calcium or angiography from CT (40,41) could be applied, the diagnostic performance may show even greater improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the CT was used only for reconstructing attenuation maps and AC in these CT AC studies. We propose that if scatter correction (39) and anatomic information such as coronary calcium or angiography from CT (40,41) could be applied, the diagnostic performance may show even greater improvement.…”
Section: Discussionmentioning
confidence: 99%
“…109,110 Diverse combinations of hybrid imaging of myocardial perfusion (CT + SPECT, CT + PET and CT + CMR) are gaining increasing interest because they provide both anatomic and functional information, improving the overall performance of the diagnostic test.…”
Section: Hybrid Devices Computed Tomography Nuclear Imagementioning
confidence: 99%
“…These characteristics make it suitable for use in patients with asthma or mild/moderate chronic obstructive pulmonary disease. 48 Schaap et al 49 have indicated that hybrid SPECT-CT images have higher specificity than either of these techniques used alone for diagnosing ischemic heart disease in populations with an intermediate or high pretest probability of having this condition.…”
Section: Nuclear Cardiologymentioning
confidence: 99%